Association between C677T polymorphism of methylene tetrahydrofolate reductase and congenital heart disease: meta-analysis of 7697 cases and 13,125 controls. - Mamasoula, C; Prentice, R; Pierscionek, T; Pangilinan, F; Mills, J; Druschel, C; Pass, K; Russell, M; Hall, D; Töpf, A; Brown, D; Zelenika, D; et al. (2013)
BACKGROUND: Association between the C677T polymorphism of the methylene tetrahydrofolate reductase (MTHFR) gene and congenital heart disease (CHD) is contentious. METHODS AND RESULTS: We compared genotypes between CHD cases and controls and between mothers of CHD cases and controls. We placed our results in context by conducting meta-analyses of previously published studies. Among 5814 cases with primary genotype data and 10 056 controls, there was no evidence of association between MTHFR C677T genotype and CHD risk (odds ratio [OR], 0.96 [95% confidence interval, 0.87-1.07]). A random-effects meta-analysis of all studies (involving 7697 cases and 13 125 controls) suggested the presence of association (OR, 1.25 [95% confidence interval, 1.03-1.51]; P=0.022) but with substantial heterogeneity among contributing studies (I(2)=64.4%) and evidence of publication bias. Meta-analysis of large studies only (defined by a variance of the log OR <0.05), which together contributed 83% of all cases, yielded no evidence of association (OR, 0.97 [95% confidence interval, 0.91-1.03]) without significant heterogeneity (I(2)=0). Moreover, meta-analysis of 1781 mothers of CHD cases (829 of whom were genotyped in this study) and 19 861 controls revealed no evidence of association between maternal C677T genotype and risk of CHD in offspring (OR, 1.13 [95% confidence interval, 0.87-1.47]). There was no significant association between MTHFR genotype and CHD risk in large studies from regions with different levels of dietary folate. CONCLUSIONS: The MTHFR C677T polymorphism, which directly influences plasma folate levels, is not associated with CHD risk. Publication biases appear to substantially contaminate the literature with regard to this genetic association.